2019
DOI: 10.1002/ejoc.201801764
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Optimal Deoxygenation Pattern of Dodecyl Glycosides for Antimicrobial Activity Against Bacillus anthracis

Abstract: The discovery of the bactericide dodecyl 2,6‐dideoxypyranoside reorganizing membrane phospholipid matrix of Bacillus species into a hexagonal phase, encouraged further research on glycone deoxygenation/bioactivity relationship. We now describe expedient syntheses of new 2‐, 3‐, 4‐deoxy, 2,3‐ and 3,4‐dideoxy glycosides in moderate to good yields. Interestingly, Amberlyst 15 is a key protagonist, efficiently applied for the transacetalation of alkyl deoxy glycosides and for ring contraction to access regioselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…The resulting mixture was extracted twice with ethyl acetate (2 Â 40 ml) and the organic phases were combined and concentrated at 303 K in vacuo to give 1,2:5,6-di-O-isopropylidene-3-deoxy--d-ribo-hexofuranose, (VII), as a colorless oil in 74% yield (1.22 g, 5.0 mmol). NMR spectral data obtained for (VII) were consistent with those reported previously (Dias et al, 2019). Dowex 50 Â 8 (200-400 mesh) ion-exchange resin (H + form) (3 g, dry weight) was added to a solution of (VII) (1.22 g, 5.0 mmol) in isopropyl alcohol (50 ml) and the resulting mixture was refluxed at 373 K for 24 h. The reaction mixture was cooled and the resin was removed by filtration.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…The resulting mixture was extracted twice with ethyl acetate (2 Â 40 ml) and the organic phases were combined and concentrated at 303 K in vacuo to give 1,2:5,6-di-O-isopropylidene-3-deoxy--d-ribo-hexofuranose, (VII), as a colorless oil in 74% yield (1.22 g, 5.0 mmol). NMR spectral data obtained for (VII) were consistent with those reported previously (Dias et al, 2019). Dowex 50 Â 8 (200-400 mesh) ion-exchange resin (H + form) (3 g, dry weight) was added to a solution of (VII) (1.22 g, 5.0 mmol) in isopropyl alcohol (50 ml) and the resulting mixture was refluxed at 373 K for 24 h. The reaction mixture was cooled and the resin was removed by filtration.…”
Section: Methodssupporting
confidence: 89%
“…The organic phases were combined and concentrated at 303 K in vacuo to give 1,2:5,6-di-O-isopropylidene-3-O-triflyl--d-ribo-hexofuranose, (VI), as a yellow solid in nearly quantitative yield (3.0 g, 7.7 mmol). NMR spectral data obtained for (VI) were consistent with those reported previously (Dias et al, 2019;Russell et al, 1990).…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…Among the most promising compounds reported, compound 7 (Scheme 1) stood out as the bactericide with the lowest minimum inhibitory concentration (MIC) against all tested species, including Bacillus anthracis Sterne, pathogenic and ovine strains, as well as Enterococcus feacalis and Bacillus cereus (MIC 12.6 μM for all), and acceptable toxicity in intestinal and hepatic cell models after a 48 hour-long exposure (IC 50 50 μM in Caco-2 cells and > 100 μM in HepG2 cells, respectively). [25,26] Further studies suggested that this class of compounds has a low propensity for the development of AMR mechanisms induced by serial passage on gradient concentrations, as well as low susceptibility to common resistance mechanisms against erythromycin, penicillin, vancomycin, ciprofloxacin, and tetracycline. With a relatively good therapeutic window corroborated by the observed selectivity of these compounds towards PE compared to phosphatidylcholine (PC) -the main phospholipid in mammalian membranes, the 4,6deoxygenation pattern of compound 7 was considered the key Scheme 1.…”
Section: Bactericidesmentioning
confidence: 99%
“…Their cytotoxicity, however, increases with an increasing chain length of the aglycon 10 . The number of reports dealing with the antimicrobial activity of alkyl glycosides is rare [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%